Place of Death of People With Cancer in 12 Latin American Countries: A Population Study Using National Death Registers - Alisa Dannenberg; Joachim Cohen; Luc Deliens; Katja Seitz; Alicia Krikorian; Luis Fernando Rodrigues; Verónica Kramer; Alejandra Sosa Basaistegui; Alberto Alonso Babarro; Andrea Cartin; Celina Castaneda; Lesly Peralta; et al. (Cancer Medicine, 2025)
ABSTRACT Background Cancer is one of the leading causes of death in Latin America. This study aims to compare the percentage of home and hospital deaths among cancer patients in 12 Latin American countries and to examine associated factors. Methods We carried out a population‐level observational study using death certificate data from Argentina, Brazil, Chile, Colombia, Costa Rica, Ecuador, El Salvador, Guatemala, Mexico, Paraguay, Peru and Uruguay. Data from cancer decedents (ICD‐10 C00–C97) for a full year (January 1 to December 31) with available data (2016–2018) were included. We used descriptive statistics and multivariable binary logistic regression analysis in each country and between countries to describe the distribution in place of death and examine associated sociodemographic, clinical and ecological factors. Results Cancer was the underlying cause of 491,929 deaths. An average of 31.1% occurred at home, from a range of 14.9% in Brazil to 81% in Guatemala. The variation remains after controlling for sociodemographic factors and cancer types. Patients who are older, live in rural areas, have lower educational levels, and a solid cancer history are more likely to die at home. Countries with more hospital beds and physicians, better Universal Health Coverage, higher Human Development Index, and higher health expenditure per capita had fewer home deaths. Conclusion Factors affecting place of death patterns in Latin America are country‐specific and the results can only partially be explained by sociodemographic, clinical and ecological factors. Our results may be used to improve palliative care according to the current country‐specific distribution of place of death.